The Legal Rules For Electronic Commercial Arbitration In Algeria - Lassoued Moussa (جامعة الوادي University of Eloued, 2024)
There is no doubt that electronic arbitration has become a system that cannot be ignored in the digital age and in light of the increasing number of legal transactions that take place online. This is due to the growing need for it, and the fact that the general rules of traditional arbitration do not fit relatively with electronic arbitration. In the absence of specific provisions for the latter, it is necessary to deduce and amend the legal rules to keep pace with the rapid development in the field of technology and the world of communications. Despite the fact that some modern legislations have issued laws related to electronic commerce, such as the Algerian legislator as a model, this study aims to find alternatives to them because electronic arbitration is an effective and successful legal system. In addition to that, it is necessary to follow up on technological development and confront it with legal rules that are compatible with it through the codification of electronic arbitration within a comprehensive legal system.
Keywords: Electronic Arbitration; Commercial Contracts; Legal System; E-commerce